Second law analysis for sustainable heat and energy transfer: The entropic potential concept. (1st February 2015) - Wenterodt, Tammo; Redecker, Christoph; Herwig, Heinz
Highlights: A new concept for process assessment is introduced. Entropy based assessment criteria are introduced. The new concept is applied to a plate heat exchanger as an example. Abstract: The choice of an assessment criterion for heat exchangers is crucial regarding the sustainability of processes and has troubled engineers for decades. In this paper it is shown that the basis for a physically meaningful assessment of every energy transfer (including conversions from one form of energy to another) lies in the correct interpretation of entropy generation. First it is shown that the effect of components in energy transfer situations on the available work (e.g. the power outcome of a working process) results from the flows of energy and entropy and the generation of entropy in a component. Next the entropic potential loss number assessment criterion is introduced, based on the entropic potential of an energy flow. It is explained how this universal criterion allows the assessment of arbitrary situations in energy transfer, illustrated by showing the advantages over the often used thermo-hydraulic performance parameter. Two examples show how the concept can be applied in numerical assessments and optimizations of heat exchangers and other components as well as in the assessment of processes.